Modeling and experimental validation of residential cyclic loads. (June 2018) - Lamberti, Francesco; Calderaro, Vito; Galdi, Vincenzo; Piccolo, Antonio
Highlights: We propose a discrete-time version of the ZIP model (DT-ZIP model). The formulation is based on measurements collected in real operating conditions. DT-ZIP model can represent residential cyclic loads (i.e. thermostatic appliances). We present a comparison with the classic ZIP model to test our proposal. Abstract: The development of strategies that involves the participation of demand for increasing the flexibility of power systems requires defining accurate residential load models. The work proposes a new model for cyclic loads characterized by different operating cycles. Here, we propose a discrete-time version of the ZIP model. The proposed model is developed starting from the collection of measurements gathered in real operating conditions from a washing machine. The subsequent statistical and clustering analysis allows the model to be generalized for cyclic appliances. A comparison with the classic ZIP model is carried out to evaluate the performances in terms of energy consumptions and active power absorption. Results show that the proposed model simulates more reliably the real behavior of cyclic loads.